Gut microbiota and colorectal cancer. (December 2016) - Yamamoto, Mayuko; Matsumoto, Satoshi
Abstract The mucosal immune system is unique to the gastrointestinal mucosa, in which a large number of immune cells are located and exert multiple functions. Meanwhile, ~100 trillion microorganisms are thought to co-inhabit in the gastrointestinal tract. Furthermore, immune cells and gut microbiota have a mutual influence and the maintenance of this symbiotic relationship results in gut homeostasis. A recent study suggested that a disturbance of gut microbiota—so called "dysbiosis"—is related to various diseases, such as inflammatory bowel disease (IBD) and colitis-associated cancer (CAC). In this review, we discuss the relationship between gut microbiota and the mucosal immune system with regard to the development of IBD and CAC. In addition, we elucidate the possibility of probiotics in treatment against these diseases.